2016
DOI: 10.4102/aveh.v75i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low vision services on the quality of life of low vision patients in Ghana

Abstract: Patients’ perspectives on the impact of clinical interventions have been recognised as critical elements in patient care. Quality-of-life instruments are designed to measure these perspectives. We used the National Eye Institute’s 25-item Visual Function Questionnaire (NEI VFQ) to measure the impact of optical low vision devices on the quality of life of 22 low vision patients who obtained and were using low vision devices from a secondary low vision clinic in the Eastern Region, Ghana. The study employed a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…That optometrists in this study and other practitioners in other studies indicated that low vision device does not help patients with low vision much may relate to the fact that clinicians use improvement in clinical measures of visual functions as a yardstick for success in low vision service for patients. Studies have demonstrated the utility of patients' perspectives to evaluate the impact of low vision devices [28,29]. These studies indicated that optical low vision devices significantly improve the quality of life of patients with low vision despite inapparent improvement in visual acuity or other clinical measures of visual function.…”
Section: Discussionmentioning
confidence: 99%
“…That optometrists in this study and other practitioners in other studies indicated that low vision device does not help patients with low vision much may relate to the fact that clinicians use improvement in clinical measures of visual functions as a yardstick for success in low vision service for patients. Studies have demonstrated the utility of patients' perspectives to evaluate the impact of low vision devices [28,29]. These studies indicated that optical low vision devices significantly improve the quality of life of patients with low vision despite inapparent improvement in visual acuity or other clinical measures of visual function.…”
Section: Discussionmentioning
confidence: 99%
“…Stelmack 17 declared that self-reported quality of life is a significant measure of the impact of low vision rehabilitation, and it has long been recognized that visual acuity measurements do not always correlate with the actual daily performance of patients with low vision. 8 …”
Section: Discussionmentioning
confidence: 99%
“…These issues can cause limitations in performing tasks that require vision in educational, occupational, and recreational activities, and these limitations reduce the quality of life of individuals with low vision. 5 , 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…Causes include albinism, congenital cataract, congenital glaucoma, congenital idiopathic nystagmus, high refractive error, and myopic degeneration. 4,5 Etiological factors, age of onset, presence of other impairments, environmental aspects, and the interactions among these will determine the child's difficulties and delay in development. 6,7 The eye care professionals such as ophthalmologists and optometrists couldhelp visually impaired children with visual and non-visual aids.…”
Section: Introductionmentioning
confidence: 99%